LES EDITS DE LA PROVINCE DU MANIEMA ET LEUR INCIDENCE SUR LE DEVELOPPEMENT SOCIO-ECONOMIQUE ET ENVIRONNEMENTAL DE LA PROVINCE - Delinde , Issa Djumaine; Eléazar, Kakwala Bin Kalonda; Gaspard, Kamango Mobuto; Edouard, Assumani Idrisa (IJRDO - Journal of Social Science and Humanities Research, 2022)
The Constitution of the DRC grants the provincial assembly the prorogatives to legislate. Paraphrasing Charles YOAVI DREKPO D. (2007, p.154) that edicts are tools for development, we have deemed it useful in this article to verify whether at least the edicts of the province of Maniema have a socio-economic and environmental impact on the population of Maniema. After investigation, it appears that only three edicts out of 23 promulgated between 2006 and 2018 have been published in the official newspaper 'Agence Congolais de Presse'; and on the whole, they have a negative impact. This is why we suggest that all the edicts promulgated should not only be published in the official gazette but also popularised in order to allow the population of Maniema not only to know about them but also and above all to really follow up on the actions taken by their elected representatives.